VAGINAL CARRIAGE RATE OF GROUP B STREPTOCOCCUS IN PREGNANT WOMEN AND ITS TRANSMISSION TO NEONATES - Chaudhry, Bushra Yasmin; Akhtar, Naeem; Balouch, Abbas Hayat (Journal of Ayub Medical College Abbottabad, 2010)
Background: Maternal vaginal colonisation with Group B Streptococcus (GBS, Streptococcus agalactiae) at the time of delivery can cause vertical transmission to the neonate. GBS is the leading cause of sepsis, meningitis and pneumonia in the infants. Asymptomatic colonisation of the vagina with GBS varies with the geographical location. Methods: This was a cross-sectional study conducted in 2009 at Benazir Bhutto Hospital, Rawalpindi, Pakistan. Lower vaginal swabs were obtained from 200 pregnant women at the time of admission in the Gynaecology and Obstetrics Department for term, normal vaginal delivery and swabs from the skin of abdomen and ear canals of their respective neonates immediately after delivery were collected. Swabs were inoculated on blood agar and incubated aerobically and on Group B Streptococcus agar (GBS agar) and incubated anaerobically in an anaerobic jar. Identification of GBS was made on the basis of colonial morphology (Î²-haemolytic colonies on blood agar and orange pigmented colonies on GBS agar), Gram stain, catalase test and conformation was done by means of latex agglutination tests. Results: A GBS carriage rate of 8.5% among pregnant women before delivery and an acquisition rate of 53% on the abdominal skin and 18% in the ear canals by the neonates of colonised mothers were found. Conclusions: GBS colonisation in pregnant women and its transmission to the neonates is present in our population so GBS infections in the prenatal and neonatal period might not be uncommon in Pakistan, so routine screening should be carried out. Keywords: Group B Streptococcus, vaginal carriage rate, pregnant women, transmission to neonates